(untitled) (International Journal of Scientific Trends, 2024)
Cestodes live as parasites in the gastrointestinal tract of ruminants. Moniesiosis is also a cestode disease that parasitizes the small intestines of sheep and goats. As a result of this disease, animals lose weight, decrease productivity and even die. Currently, many anthelmintics belonging to the albendazole group are being produced for the treatment and prevention of monieziosis.